Morphotropic phase boundary, polymorphic phases and enhanced electrostrain/piezoelectricity in Ag1-xKxNbO3 solid-solution ceramics. Issue 10 (August 2023) - Tian, Ye; Jia, Ye; Wang, Xinyi; Li, Lei; Geng, Jia; Wang, Tong; Xu, Yonghao; Jin, Li; Bao, Yizheng; Chen, Chen; Zhang, Leiyang; Ma, Ming; et al.
Abstract: Ag1− x K x NbO3 (AKN x ( x ≤ 0.12) ceramics were prepared to understand the relationship of structure-properties driven by compositions and temperatures. The results suggested that this binary system possessed a morphotropic phase boundary (MPB) consisted of ferrielectric and ferroelectric phases with iso-symmetry at room temperature, in which domains switching together with electric-field-induced irreversible phase transition achieved a much higher electrostrain ( S max = 0.4%) than other compositions. But this MPB was destroyed after poling, leading to inferior piezoelectricity. A phase diagram was drawn after analyzing in situ XRD and dielectric data, where an almost vertical ferrielectric/antiferroelectric ↔ polymorphic ferroelectric MPB line starting from a triple point was proposed. As temperature increased, the piezoelectricity significant enhanced near ferroelectric orthorhombic ↔ monoclinic phase boundary, while the highest piezoelectricity was achieved near the monoclinic ↔ paraelectric phase boundary with d 33 = 200 pC/N. The enhanced piezoelectricity is intimately related to the ferroelectric monoclinic possessing Pm symmetry.